Pollution-induced metabolic responses in hypoxia-tolerant freshwater turtles - Venancio, Larissa Paola Rodrigues [UNESP]; Silva, Maria Isabel Afonso [UNESP]; da Silva, Tiago Lucena [UNESP]; Moschetta, Vinicius Augusto Gobbe [UNESP]; de Campos Zuccari, Débora Aparecida Pires; Almeida, Eduardo Alves [UNESP]; Bonini-Domingos, Claudia Regina [UNESP] (Elsevier, 2013)
The physiological control to support the absence of O2 for long periods of diving, and oxidative damage impact caused by the whole process of hypoxia/reperfusion in freshwater turtles is well known. However, effects of contaminants may act as co-varying stressors and cause biological damage, disrupting the hypoxia/reperfusion oxidative damage control. In order to investigate the action of environmental stressors present in domestic or industrial wastewater effluent, we performed a biochemical analysis of biotransformation enzymes, oxidative stress, as well as neuromuscular, physiological and morphological parameters in Phrynops geoffroanus, an hypoxic-tolerant freshwater turtle endemic of South America, using animals sampled in urban area, contaminated by sewage and industrial effluents and animals sampled in control area. Here we demonstrate the physiological and biochemical impact caused by pollution, and the effect that these changes cause in antioxidant activity. Animals from the urban area exhibited higher EROD (ethoxyresorufin-O-deethylase, CYP1A1), GST (glutathione S-transferase), G6PDH (glucose-6-phosphate deshydrogenase), AChE (acetilcholinesterase) activities and also TEAC (trolox-equivalent antioxidant capacity) and TBARS (thiobarbituric acid reactive substances) values. We examined whether two morphometric indices (K - condition factor and HIS - hepatosomatic index) which help in assessing the general condition and possible liver disease, respectively, were modified. The K of the urban animals was significantly decreased compared to the control animals, but the HIS value was increased in animals from the urban area, supporting the idea of an impact in physiology and life quality in the urban freshwater turtles. We propose that this freshwater turtle specie have the ability to enhance its antioxidants defenses in order to protect from tissue damage caused by hypoxia and reperfusion, but also that caused by environmental contamination and that the oxidative damage control in hypoxic conditions has resulted in an adaptive condition in hypoxic-tolerant freshwater turtle species, in order to better tolerate the release of contaminated effluents resulting from human activity. © 2013 Elsevier Inc.
Keywords: Antioxidant capacity; Contaminated effluents; Contamination biomarkers; Freswater turtles; Phrynops geoffroanus